A companion to digital art - Paul, Christiane (Wiley Blackwell companions to art history, 2016)
Reflecting the dynamic creativity of its subject, this definitive guide spans the evolution, aesthetics, and practice of today's digital art, combining fresh, emerging perspectives with the nuanced insights of leading theorists. * Showcases the critical and theoretical approaches in this fast-moving discipline * Explores the history and evolution of digital art; its aesthetics and politics; as well as its often turbulent relationships with established institutions * Provides a platform for the most influential voices shaping the current discourse surrounding digital art, combining fresh, emerging perspectives with the nuanced insights of leading theorists * Tackles digital art's primary practical challenges – how to present, document, and preserve pieces that could be erased forever by rapidly accelerating technological obsolescence * Up-to-date, forward-looking, and critically reflective, this authoritative new collection is informed throughout by a deep appreciation of the technical intricacies of digital art